Finite Element Based Modeling of a Piezolaminated Tapered Beam for Voltage Generation. (2016) - Biswal, Alok Ranjan; Roy, Tarapada; Behera, Rabindra Kumar; Parida, Pramod Kumar; Pradhan, Saroj Kumar
Abstract: The present article deals with finite element (FE) based modeling of a nonprismatic piezolaminated cantilever beam for voltage generation. The beam is modeled using the Euler-Bernoulli beam formulation. The governing equation of motion is derived by using the Hamilton's principle. In order to solve the governing equation two noded beam element with two degrees of freedom (DOF) per node is considered. In this work the effect of structural damping is incorporated in the finite element model. The effects of taper (both in width and height direction) on output voltage are discussed as well.